The expression of the embryonic gene Cripto‐1 is regulated by OCT4 in human embryonal carcinoma NCCIT cells. Issue 1 (22nd December 2017) - Park, Sung‐Won; Do, Hyun‐Jin; Han, Mi‐Hee; Choi, Wonbin; Kim, Jae‐Hwan
Abstract : Cripto‐1 and OCT4, expressed in stem cells and cancers, play important roles in tumorigenesis. Here, we demonstrate that Cripto‐1 expression is regulated by OCT4 in human embryonic carcinoma NCCIT cells. The endogenous expression of Cripto‐1 and OCT4 is significantly reduced during differentiation. Cripto‐1 expression is increased by OCT4 overexpression, but decreased by shRNA‐mediated OCT4 knockdown. OCT4 overexpression significantly activates Cripto‐1 transcriptional activity. A 5′‐upstream minimal promoter sequence in the gene‐encoding Cripto‐1 is significantly activated by OCT4 overexpression. Mutation of the putative OCT4‐binding site abolishes OCT4‐mediated activation of the Cripto‐1 promoter. The OCT4 transactivation domains mediate transcriptional activity of the Cripto‐1 minimal promoter through direct interaction. Taken together, OCT4 plays an important role as a transcriptional activator of Cripto‐1 expression in NCCIT cells. Abstract :